Perceptions of community college presidents: total quality management performance measures at their colleges - Riccardi, Mark Timothy, author; Makela, Carole J., advisor; Venneberg, Donald L., advisor; Folkestad, James E., committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2009)
Continuous Quality Improvement (CQI) measures such as Total Quality Management (TQM), Strategic Planning, Six Sigma, and the Balanced Scorecard are often met with skepticism among leaders of higher education. This study attempts to fill a gap in the literature regarding the study of relationships among specific variables, or building blocks, associated with TQM and their use within community colleges. Presidents at public, private, and tribal community colleges from every state and U.S. territory were surveyed to determine their perceptions regarding the presence of TQM performance measures at their college. These performance measures were building blocks of the variables under study. These independent variables were: (a) leadership, (b) continuous improvement, (c) employee fulfillment, (d) learning, (e) process management, (f) cooperation, and (g) customer focus. The dependent variables were: (a) product/service quality, (b) financial effectiveness, (c) operational efficiency, (d) public responsibility, (e) customer satisfaction, and (f) employee satisfaction. A total of 179 responses were received from the pilot and main studies and statistical analysis evaluated six hypotheses under study. The findings indicated that the presidents perceived at their colleges relationships existed between product/service quality and customer focus (H1), financial effectiveness and the other variables (H2), operational efficiency and continuous improvement (H3), public responsibility and the other variables (H4), customer satisfaction and employee fulfillment, cooperation, customer focus, and public responsibility (H5), and between employee satisfaction and the other variables (H6). This study adds to the field of research by allowing CQI practitioners to focus on those TQM variables that support each other. Implications for future study include the evaluation of leadership during a CQI process, how accepting or resistant individuals are to change, and an exploration of how integral TQM may be within institutions, whether identified or labeled as such.
Department Head: Sharon K. Anderson.